Instrumental resolution as a function of scattering angle and wavelength as exemplified for the POWGEN instrument. Issue 3 (25th May 2017) - Jacobs, Philipp; Houben, Andreas; Schweika, Werner; Tchougréeff, Andrei L.; Dronskowski, Richard
Abstract : A fundamental description of the instrument resolution file is elaborated for the angular‐ and wavelength‐dispersive cases of Rietveld refinement, exemplified for the POWGEN instrument. It is shown how to refine the necessary profile function parameters from a dataset measured on a diamond reference sample. The analysis is performed in a two‐dimensional refinement space based on the convenient variables d and d ⊥ . Abstract : The method of angular‐ and wavelength‐dispersive ( e.g. two‐dimensional) Rietveld refinement is a new and emerging tool for the analysis of neutron diffraction data measured at time‐of‐flight instruments with large area detectors. Following the approach for one‐dimensional refinements (using either scattering angle or time of flight), the first step at each beam time cycle is the calibration of the instrument including the determination of instrumental contributions to the peak shape variation to be expected for diffraction patterns measured by the users. The aim of this work is to provide the users with calibration files and – for the later Rietveld refinement of the measured data – with an instrumental resolution file (IRF). This article will elaborate on the necessary steps to generate such an IRF for the angular‐ and wavelength‐dispersive case, exemplified for the POWGEN instrument. A dataset measured on a standard diamond sample is used to extract the profile function in the two‐dimensional case. It is found that the variation of reflection width with 2gθ and λ can be expressed by the standard equation used for evaluating the instrumental resolution, which yields a substantially more fundamental approach to the parameterization of the instrumental contribution to the peak shape. Geometrical considerations of the POWGEN instrument and sample effects lead to values for Δgθ, Δ t and Δ L that yield a very good match to the extracted FWHM values. In a final step the refinement results are compared with the one‐dimensional, i.e. diffraction‐focused, case.